Commentary on "Two studies of Autonomous Sensory Meridian Response (ASMR): The Relationship between ASMR and Music-Induced Frisson" by Alexsandra Kovacevich and David Huron - Ruth, Nicolas (Empirical Musicology Review, 2019)
No abstract available.